Fused Filament Fabrication-Based Additive Manufacturing of Commercially Pure Titanium - Thompson, Yvonne; Polzer, Markus; Gonzalez-Gutierrez, Joamin; Kasian, Olga; Heckl, Johannes Philipp; Dalbauer, Valentin; Kukla, Christian; Felfer, Peter (Advanced Engineering Materials, 2021)
Fabrication of titanium components is very cost intensive, partly due to the complex machining and limited recyclability of waste material. For electrochemical applications, the excellent corrosion resistance of pure titanium is of high importance, whereas medium mechanical strength of fabricated parts is sufficient for such a use case. For smaller parts, metal fused filament fabrication (MF3) enables the fabrication of complex metallic structures densified during a final sintering step. Pure titanium can be processed to near-net-shape geometries for electrochemical applications if the parameters and the atmosphere during sintering are carefully monitored. Herein, the influence of thermal debinding and sintering parameters on the fabrication of high-density pure titanium using MF3 is investigated. Particular focus is placed on enhancing sintered density while limiting impurity uptake to conserve the high chemical purity of the initial powder material. Relative densities of 95% are repeatedly reached inside the bulk of the samples. An oxygen content of 0.56 wt% as a result of vacuum processing induces the formation of the retained α-Ti phase (925 HV0.2) inside the α matrix (295 HV0.2). Fabricated parts exhibit high mechanical strength, albeit reduced elongation due to remaining pores, and, in terms of electrochemistry, enhanced stability toward anodic dissolution.
CRIS-Team Scopus Importer:2021-10-01
Keywords: additive manufacturing; highly filled filaments; material extrusion; powder metals; sintering

Fused filament fabrication, debinding and sintering as a low cost additive manufacturing method of 316L stainless steel - Thompson, Yvonne; Gonzalez-Gutierrez, Joamin; Kukla, Christian; Felfer, Peter (Additive Manufacturing, 2019)
By using filaments comprising metal or ceramic powders and polymer binders, solid metal and ceramic parts can be created by combining low-cost fused filament fabrication (FFF) with debinding and sintering. In this work, we explored a fabrication route using a FFF filament filled with 316 L steel powder at 55 vol.-%. We investigated the printing, debinding and sintering parameters and optimized them with respect to the mechanical properties of the final part. Special focus was placed on debinding and sintering in order to obtain components of low residual porosity. Solvent debinding of the printed green bodies created an internal network of interconnected pores and was followed by thermal debinding. Thermal debinding allowed for complete removal of the remaining binder and produced mechanically stable brown parts. Sintering at 1360 °C provided densification of the parts and generated nearly isotropic linear shrinkage of about 20%. Using optimized parameters, it was possible to fabricate 316 L steel components with a density greater than 95% via the material extrusion additive manufacturing, debinding and sintering route, with achievable deflections in a 3-point bending test similar to rolled sheet material, albeit at lower strength.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Additive manufacturing; Highly filled filaments; Material extrusion; Powder metals; Sintering

Metal fused filament fabrication of the nickel-base superalloy IN 718 - Thompson, Yvonne; Zissel, Kai; Förner, Andreas; Gonzalez-Gutierrez, Joamin; Kukla, Christian; Neumeier, Steffen; Felfer, Peter (Journal of Materials Science, 2022)
This study demonstrates metal fused filament fabrication (MF3) as an alternative additive and highly flexible manufacturing method for free-form fabrication of high-performance alloys. This novel processing, which is similar to Metal injection molding (MIM), enables a significant reduction in manufacturing costs for complex geometries, since expensive machining can be avoided. Utilizing existing equipment and reducing material expense, MF3 can pave the way for new and low-cost applications of IN 718, which were previously limited by high manufacturing costs. Iterative process optimization is used to find the most suitable MF3 process parameters. High relative density above 97% after pressureless sintering can be achieved if temperature profiles and atmospheres are well adjusted for thermal debinding and sintering. In this study, the influence of processing parameters on the resulting microstructure of MF3 IN 718 is investigated. Samples sintered in vacuum show coarse-grained microstructure with an area fraction of 0.36% NbC at grain boundaries. Morphology and composition of formed precipitates are analyzed using transmission electron microscopy and atom probe tomography. The gamma/gamma ''/gamma' phases' characteristics for IN 718 were identified. Conventional heat treatment is applied for further tailoring of mechanical properties like hardness, toughness and creep behavior. Fabricated samples achieve mechanical properties similar to MIM IN 718 presented in literature.
CRIS-Team WoS Importer:2022-02-11

Powder content in powder extrusion moulding of tool steel: Dimensional stability, shrinkage and hardness - Gonzalez-Gutierrez, Joamin; Thompson, Yvonne; Handl, David; Cano, Santiago; Schuschnigg, Stephan; Felfer, Peter; Kukla, Christian; Holzer, Clemens; Burkhardt, Carlo (Materials Letters, 2021)
Powder extrusion moulding (PEM) is a versatile and cost-effective technology for producing bidimensional shapes, (e.g. tubes and profiles) from metals, ceramics and cermets. PEM quality is affected by powder content; therefore, three highly-filled polymeric compounds containing 50, 55, 60 vol% tool steel powder were prepared and extruded to profiles. Extruded parts were debound in cyclohexane and sintered in forming gas (Ar + 5% H-2) to obtain dense, sintered parts. The dimensional stability, the shrinkage and the hardness were measured. Minimum shrinkage and higher dimensional stability were obtained when the powder content was the highest (60 vol%). Specimens with 50 vol% powder had the highest hardness due to the initial higher binder content and resulting carbon content. (C) 2020 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2021-01-08

Steel parts produced by material extrusion additive manufacturing, solvent debiding and sintering - Gonzalez-Gutierrez, Joamin; Thompson, Yvonne; Cano, Santiago; Felfer, Peter; Kukla, Christian; Holzer, Clemens (MS and T 2019 - Materials Science and Technology 2019, 2019)
CRIS-Team Scopus Importer:2019-12-03